PREPARING 21ST CENTURY STUDENTS: WORLD LITERATURE+PROJECT-BASED LEARNING+ ICT USE IN CLASS - IDA ROSMALINA (Sriwijaya University Learning and Education International Conference, 2016)
The 21st Century Skils are a set of abilities that students need to develop in order to succeed in this information age. Partnership for 21st Century Skills lists three different areas of skills to be developed; learning skills, literacy skills, and life skills. This paper aims at describing how World Literature (WL), Project-Based Learning (PBL), and Information and Communication Technology (ICT) could be integratedly implemented in English Language Teaching (ELT) to help students improve their English mastery in general and ultimately prepare them to become 21st century students. This teaching approach refers to an extensive reading assignment given to students in groups of 3 to 5 within a limited time after their formal reading class. There are at least three major uses of this approach: to increase students’ learning skills (critical thinking, creative thinking, collaboration), to enahnce their literacy skills knowledge (exploring the world literature online), and to improve their life skills (productive English language skills). In this appproach the students are required to present a summary of their group work either in writing or in speaking. At the same time they also have to connect any related materials to their story; a song, another similar story from a different country, a film, or else to show their understanding of the materials and how broad their knowledge of the world in relation to the content of the literature.